Hábito alimentar em Calliphoridae (Insecta, Diptera, Oestroidea) : bionomia e bases moleculares = Feeding habit in Calliphoridae (Insecta, Diptera, Oestroidea): bionomy and molecular basis - Faria, Gustavo Amaral, 1995- (2019)
Orientadores: Patricia Jacqueline Thyssen, Tatiana Teixeira Torres